Indonesian undergraduate students’ perceptions of problem-based learning implementation in an ELT class: A small-scale survey - Juver, Zalfah Ananda; Prasetya, Willy (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
This study aimed at identifying Indonesian undergraduate studentsâ€™ perceptions of Problem-Based Learning (PBL) implementation in an English language education department at a private university in Indonesia. Using total population sampling, 74 students who were taking a language classroom management course in which PBL was implemented through collaborative work were involved in this survey study.Â Â The data were collectedÂ using a 21-itemÂ questionnaire from Jaeger and Adair (2014) that was based on Senocak (2009). The data were then analyzed statistically to identify the participating studentsâ€™ perceptions of PBL implementation by interpreting the patterns of the data. Based on the results of this study, the participants tended to perceive that PBL helped them become more self-directed. However, many of them felt that the collaborative work implemented in PBL was more a difficulty than an ease. The implication of this study is also discussed. DOI:Â 10.26905/enjourme.v7i2.9032